PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTS NAHDIYAH TAPUNG HILIR - Rini Ekawati; Titi Solfitri; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to improve the learning process and improve the learning outcomes of students of class VIII MTS Nahdiyah Tapung Hilir odd semester of the academic year 2017/2018. Form of research conducted is action research (PTK) with 2 cycles. The subjects consisted of 14 male students and 21 female students with heterogeneous ability. Instrument in this research of development there are 2 that is learning devuce and instrument dara collection. Instrument of data collection in this research is observation sheet and test of mathematics learning result. The observation sheets were analyzed descriptively qualitatively, while the mathematics learning outcomes were analyzed descriptively quantitatively. From the qualitative analysis it can be seen that there is improvement of learning process from before action to cycle I and cycle II. Students are seen actively participating and becoming more independent in the learning process. The results of this study indicate the number of students who reached the KKM increased from the basic score of 16 students (45.71%) to UH I amounted to 28b people 80%) and UH 2 amounted to 31 people (88,57%)..The result of this research shows that applying cooperative learning model of Numbered Heads Together (NHT) approach can improve learning process and can remind learning result mathematics students of class VIII MTS Nahdiyah Tapung Hilir academic year 2017/2018 on the subject matter of analyze data besed on data attribution, mean, median, mode and data distribution to take conclusion. And explain the empirical an theoretical opportunies of an event from an experiment.Keywords: Mathematics learning outcomes, Cooperative learning, Numbered Heads Together (NHT), Classroom Action Research.